Can China realise its energy-savings goal by adjusting its industrial structure?. Issue 2 (2nd April 2016) - Yu, Shiwei; Zheng, Shuhong; Ba, Guizhi; Wei, Yi-Ming
ABSTRACT: To investigate whether China can realise its energy-savings goal by 2020 through adjustments to its industrial structure, this study proposes a dynamic input–output multi-objective optimisation model. According to this model, the objectives to be achieved include the maximum gross domestic product and employment, and the minimum energy consumption, where the constraints are the sectoral dynamic input–output balance, labour and energy supply, and sectoral production capacity. The four best solutions are screened from the Pareto-optimal front. The study findings show that the energy intensities in 2020 would decrease by 42.8%, 43.5%, 42.9%, and 43.4% in the four scenarios when compared to their 2002 levels. This means that China can fully achieve its planned energy-savings target for 2020. In order to ensure that the industrial structure is optimised for the future, sectoral capital investments should be regulated by China's government and efforts to improve energy efficiency should be maintained.